1) решим систему:
a+b=4\1
ab=-6\1
a+b=4
ab=-6
a=4-b
(4-b)*b=-6
4b-b^2=-6
Подставим полученные пары корней в данное выражение:8a-2b(3a-4b):
1)
2)
вроде все) ; ну и задачка(
1) решим систему:
a+b=4\1
ab=-6\1
a+b=4
ab=-6
a=4-b
(4-b)*b=-6
a=4-b
4b-b^2=-6
a=4-b
Подставим полученные пары корней в данное выражение:8a-2b(3a-4b):
1)![8(2+\sqrt{10})-2(2-\sqrt{10})(3(2+\sqrt{10})-4(2-\sqrt{10}))=164-24\sqrt{10}](/tpl/images/0120/3299/4e703.png)
2)![8(2-\sqrt{10})-2(2+\sqrt{10})(3(2-\sqrt{10})-4(2+\sqrt{10}))=164+24\sqrt{10}](/tpl/images/0120/3299/07d1c.png)
вроде все) ; ну и задачка(